Ancient small-tank irrigation in Sri Lanka: continuity and change - Shah, Tushaar; Samad, Madar; Ariyaratne, Badugodahewa Ranjith; Jinapala, K. (2013)
This paper shows that winds of change are blowing in the dry zones of north-central Sri Lanka, the original hydraulic civilisation of the world. The social organisation of tank irrigation - which for centuries had combined a stylised land-use pattern, a system of highly differentiated property rights, and elaborate rules of community management of tank irrigation -has now been morphing in response to demographic pressures, market signals, technical change and modernisation. What are the lessons for south Asia and Sub-Saharan Africa?